A systematic review and meta-analysis of double trophectoderm biopsy and/or cryopreservation in PGT: balancing the need for a diagnosis against the risk of harm - Li Piani, Letizia; Petrone, Pasquale; Brutto, Mariafrancesca; De Vos, Anick; Van Der Kelen, Annelore; Vaiarelli, Alberto; Rienzi, Laura; Conforti, Alessandro; Cimadomo, Danilo; Verpoest, Willem (Human reproduction update, 2025)
To prevent the transfer of embryos affected by monogenic conditions and/or chromosomal defects, preimplantation genetic testing (PGT) requires trophectoderm biopsy and cryopreservation. In 2-6% of biopsies, the diagnosis may be inconclusive due to DNA amplification failure or low-quality results. In these cases, a round of re-warming, re-biopsy, and re-cryopreservation is required to obtain a genetic diagnosis. In other cases, when the IVF centre starts providing PGT and/or when the patients develop an indication because of multiple failures, miscarriages or the birth of an affected child after IVF, cryopreserved untested embryos may be warmed, biopsied, and then re-vitrified. However, it is still unclear whether multiple manipulations may reduce reproductive outcomes after PGT. This study aimed at conducting a systematic review to investigate the available evidence on the safety of double biopsy and/or double cryopreservation-warming and provide recommendations in this regard. We performed meta-analyses of the differences in the reproductive outcomes (live birth per embryo transfer [LBR per ET], clinical pregnancy rate per ET [CPR per ET], and miscarriage rate per clinical pregnancy [MR per CP]) in double cryopreservation and single biopsy (CBC) or double biopsy and double cryopreservation (BCBC) flows vs the control single biopsy and single cryopreservation (BC) flow. Cryo-survival rates before ET and gestational and perinatal outcomes were also reported. PRISMA guidelines were followed to gather all available information from the literature (PubMed, Scopus, and Embase). We used Medical Subject Headings (MeSH) terms and a list of specific keywords relevant for the study question. We searched for original studies in humans, published in peer-reviewed journals in English up to April 2024. Four independent authors assessed the articles for inclusion. One included paper was retrieved from another source. A total of 4219 records were identified, and 10 studies were included in the meta-analysis. Certainty of evidence level ranged from low to moderate. Both the CBC and BCBC groups showed reduced reproductive outcomes compared to the control (BC). Specifically, live birth rates per embryo transfer were lower in the CBC group (OR: 0.56, 95% CI: 0.38-0.81, I2 = 58%; six studies) and the BCBC group (OR: 0.51, 95% CI: 0.34-0.77, I2 = 24%; six studies). CPR per ET were also lower in the CBC group (OR: 0.68, 95% CI: 0.51-0.92, I2 = 57%; seven studies) and the BCBC group (OR: 0.60, 95% CI: 0.46-0.78, I2 = 0%; seven studies). Additionally, MR per CPs were higher in both the CBC group (OR: 1.68, 95% CI: 1.02-2.77, I2 = 50%; seven studies) and the BCBC group (OR: 2.08, 95% CI: 1.13-3.83, I2 = 28%; seven studies). Cryo-survival as well as gestational and perinatal outcomes were within the expected norms in the studies reporting them. Improved genetic technologies, standardization of laboratory protocols, operators' proficiency with biopsy and cryopreservation, and continuous monitoring of the performance are essential to minimize inconclusive diagnoses and the putative impact of additional embryo manipulations. Although poorer reproductive outcomes might result from double biopsy and/or double cryopreservations, these practices may still be worthwhile to avoid transferring affected/aneuploid blastocysts. Therefore, the risks must be weighed against the potential benefits for each specific couple. PROSPERO (ID: CRD42024503678).